Urban refugia enhance persistence of an endangered endemic keystone lizard threatened by the rapid spread of an invasive predator - Marc Vez-Garzón; Sandra Estela Moreno-Fernández; Guillem Casbas; Víctor Colomar; Oriol Lapiedra (Global Ecology and Conservation, 2025)
Urbanization shapes global patterns of biodiversity. While often driving biodiversity loss and biotic homogenization, urban areas could paradoxically act as refugia for species threatened by other global change drivers, such as biological invasions. Despite growing interest in their conservation potential, a lack of robust empirical studies unveiling how urban refugia emerge and contribute to species persistence hinders our ability to leverage urban areas to minimize global biodiversity loss. Here, we examined whether and how urban areas promote the persistence of a keystone, endangered endemic Mediterranean island lizard (Podarcis pityusensis) threatened by a rapidly spreading invasive snake (Hemorrhois hippocrepis). By integrating field transects, citizen science data, snake trapping, and population dynamics models, we show that invasive snakes drive rapid lizard extirpation in natural areas, but urbanization buffers this effect, enabling local persistence. Intensive snake trapping revealed that urbanization hinders snake spread, acting as an ecological filter. Finally, population dynamics models show that, contrary to a source-sink model, urban lizard populations can persist in the mid-term without immigration, as surrounding peri-urban populations have collapsed under sustained predation pressure by the invasive snake. Our findings provide empirical evidence of how urban areas can effectively act as refugia for threatened species, emphasizing their importance in global biodiversity conservation strategies.